Metalloproteinases as biochemical markers of pregnancy pathology - K. N. Grigorieva; V. O. Bitsadze; J. Kh. Khizroeva; M. V. Tretyakova; D. V. Blinov; N. A. Makatsariya; V. I. Tsibizova; I. A. Nakaidze; N. R. Gashimova; E. Grandone; A. D. Makatsariya (Акушерство, гинекология и репродукция, 2022)
The success in modern biology has significantly enriched scientific understanding of the pathogenetic basis underlying some diseases, including obstetric and gynecological practice. Despite this, the etiology and pathogenesis of some conditions are not yet fully elucidated. One of the approaches is to study metalloproteinases during pregnancy, particularly concerning occurrence of formidable complication such as preeclampsia, which diagnostics and significance have been continuously revised. Preeclampsia is a disease that leads altered course of pregnancy, and sometimes even to maternal and/or fetal death. Currently, no specific treatment for preeclampsia has been proposed, but early prognosis is crucial for a more favorable maternal and fetal outcome. Given that metalloproteinase activity is able to influence trophoblast invasion and remodeling of spiral arteries, insights into such processes are of high importance.